Comparing the Outcomes of a Personalized Versus Nonpersonalized Home-Based Auditory Training Program for Cochlear Implant Users. Issue 3 (29th October 2022) - Magits, Sara; Boon, Ellen; De Meyere, Linus; Dierckx, Ann; Vermaete, Ellen; Francart, Tom; Verhaert, Nicolas; Wouters, Jan; van Wieringen, Astrid
Abstract : Objectives: Audiological rehabilitation includes sensory management, auditory training (AT), and counseling and can alleviate the negative consequences associated with (untreated) hearing impairment. AT aims at improving auditory skills through structured analytical (bottom-up) or synthetic (top-down) listening exercises. The evidence for AT to improve auditory outcomes of postlingually deafened adults with a cochlear implant (CI) remains a point of debate due to the relatively limited number of studies and methodological shortcomings. There is a general agreement that more rigorous scientific study designs are needed to determine the effectiveness, generalization, and consolidation of AT for CI users. The present study aimed to investigate the effectiveness of a personalized AT program compared to a nonpersonalized Active Control program with adult CI users in a stratified randomized controlled clinical trial. Design: Off-task outcomes were sentence understanding in noise, executive functioning, and health-related quality of life. Participants were tested before and after 16 weeks of training and after a further 8 months without training. Participant expectations of the training program were assessed before the start of training. Results: The personalized and nonpersonalized AT programs yielded similar results. Significant on-task improvements were observed. Moreover, AT generalized to improved speech understanding in noise for both programs. Half of the CI users reached a clinically relevant improvement in speech understanding in noise of at least 2 dB SNR post-training. These improvements were maintained 8 months after completion of the training. In addition, a significant improvement in quality of life was observed for participants in both treatment groups. Adherence to the training programs was high, and both programs were considered user-friendly. Conclusions: Training in both treatments yielded similar results. For half of the CI users, AT transferred to better performance with generalization of learning for speech understanding in noise and quality of life. Our study supports the previous findings that AT can be beneficial for some CI users.